The EPICA-DML Deep Ice Core A Visual Record - Faria, Sérgio Henrique (Frontiers in Earth Sciences, 2018)
The line-scan images collected in this book represent the most accurate optical record of Antarctic ice cores ever presented, providing an invaluable resource for glaciologists and climate modellers, as well as a fascinating compilation of ice core images for Antarctica enthusiasts. Global warming and the Earth's past climate are the two main reasons for extracting deep ice cores from Antarctica. Indeed, dust particles, aerosols and other climatic traces deposited on the snow surface, as well as the air trapped in bubbles by compacted snow, produce chronologically ordered strata, making the ice from Antarctica the most accurate and valuable archive of the Earth's climate over the last million years. In addition, the layered structure produced by these strata, when revealed by appropriate methods, provides indispensable information concerning the flow and mechanical stability of the Antarctic ice sheet, allowing us to assess the current and future impact of global warming on the melting of polar ice caps with much greater precision.